Procalcitonin kinetics – prognostic and diagnostic significance in septic patients - Lipińska-Gediga, Małgorzata (Arch Med Sci, 2016)
INTRODUCTION: Severe sepsis and septic shock are advanced clinical conditions representing the patient's response to infection and having a variable but high mortality rate. Early evaluation of sepsis stage and choice of adequate treatment are key factors for survival. Some study results suggest the necessity of daily procalcitonin (PCT) monitoring because of its prognostic and discriminative value. MATERIAL AND METHODS: An observational and prospective study was conducted to evaluate the prognostic and discriminative value of PCT kinetics in comparison to PCT absolute value measurements. In a group of 50 intensive care unit patients with diagnosis of severe sepsis or septic shock, serum PCT measurements were performed on admission, and on the 2(nd), 3(rd) and 5(th) day of therapy. The level of PCT was determined with a commercially available test according to the manufacturer's protocol. RESULTS: The kinetics of PCT assessed by ΔPCT was statistically significant in the survivors vs. the non-survivors subgroup (ΔPCT(3/1), p = 0.022; ΔPCT(5/1), p = 0.021). ΔPCT has no statistical significance in the severe sepsis and septic shock subgroups for all analyzed days. Only the 5(th) day PCT level was significantly higher in the non-survivors vs. survivors group (p = 0.008). The 1(st) day PCT level in the severe sepsis vs. septic shock group has a discriminative impact (p = 0.009). CONCLUSIONS: According to the results, single serum PCT measurement, regardless of absolute value, has a discriminative impact but no prognostic significance, during the first 2 days of therapy. The PCT kinetics is of prognostic value from the 3(rd) day and is of earlier prognostic significance in comparison to changes in the patient's clinical condition evaluated by SOFA score kinetics.